2022
DOI: 10.1186/s12711-022-00757-z
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the genetic resistance to paratuberculosis in Holstein cattle via single-step genomic evaluation

Abstract: Background Bovine paratuberculosis, or Johne’s disease (JD), is a contagious and incurable disease caused by Mycobacterium avium subsp. paratuberculosis (MAP). It has adverse effects on animal welfare and is very difficult to control, leading to serious economic consequences. An important line of defense to this disease is host genetic resistance to MAP, which, when it will be more fully understood, could be improved through selective breeding. Using a large dataset of Holstein cows (161,253 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…It has proven difficult to establish a MAP infection through an oral route in mice or to generate clinical signs and intestinal lesions. Species-specific attenuation of mutant strains is consistent with previous literature (Scandurra et al, 2010;Bannantine et al, 2014b) where evaluation of MAP 1566 live-attenuated vaccine strain in mouse model indicated some level of protection against challenge, while the evaluation of same vaccine strains was unable to show promising results in goat model (Bannantine et al, 2014b). In present study, the opposite is observed where vaccine strains were not attenuated for colonization in mice tissue, while they were both attenuated for colonization in natural host.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has proven difficult to establish a MAP infection through an oral route in mice or to generate clinical signs and intestinal lesions. Species-specific attenuation of mutant strains is consistent with previous literature (Scandurra et al, 2010;Bannantine et al, 2014b) where evaluation of MAP 1566 live-attenuated vaccine strain in mouse model indicated some level of protection against challenge, while the evaluation of same vaccine strains was unable to show promising results in goat model (Bannantine et al, 2014b). In present study, the opposite is observed where vaccine strains were not attenuated for colonization in mice tissue, while they were both attenuated for colonization in natural host.…”
Section: Discussionsupporting
confidence: 91%
“…Current control strategies focus on preventing the transmission of MAP through management practices ( Barkema et al., 2018 ) by testing and culling positive animals, decreasing the incidence of new infections, preventing spread, and protecting negative herds, and decreasing prevalence in bulk tank milk ( Wolf et al., 2014 ). Identifying and selectively breeding cattle with natural resistance to MAP infection is also an approach recently employed by Canada and some European countries ( Alonso-Hearn et al., 2022 ; Sanchez et al., 2022 ). Despite considerable efforts to control Johne's disease, their effectiveness has been limited mostly due to high costs, suboptimal diagnostics, and incomplete knowledge of MAP pathogenesis ( Nielsen and Toft, 2006 ; Nielsen and Toft, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the significant region on OAR20 identified by LDLA analysis, maps close to a region that affects the resistance to gastro‐intestinal nematodes detected in the same experimental population [ 79 ]⁠. Moreover, the orthologous region on bovine chromosome 23 has been found to be significantly associated with resistance to PTB in most of the recent GWAS performed with high-density SNP genotypes or imputed whole-genome sequences [ 29 , 30 , 39 , 40 , 80 , 81 ]. In our population, this region explains a relevant portion of the genetic variance for both variables and could be exploited in selection schemes.…”
Section: Discussionmentioning
confidence: 99%
“…The role of host genetics in susceptibility to MAP infection has been largely studied in cattle. As reviewed by Brito et al [ 21 ], heritability estimates for this trait in this species ranged from 0.03 to 0.57 depending on the diagnostic tests, statistical models and populations [ 22 30 ]. Moreover, several genome-wide association studies (GWAS) have been carried out and numerous quantitative trait loci (QTL) have been mapped on nearly all the bovine chromosomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation